1993
DOI: 10.1017/s0022215100122662
|View full text |Cite
|
Sign up to set email alerts
|

Larynx preservation after initial non-cisplatin containing combination chemotherapy plus radiotherapy, as opposed to surgical intervention with or without radiotherapy in previously untreated advanced head and neck cancer: final analysis after 12 years follow-up

Abstract: After a median follow-up of 12 years, median overall survival of 73 patients with advanced squamous cell carcinoma of the larynx was 65 months. The 61 per cent of patients responding to two courses of initial schedule A combination chemotherapy, not including cisplatin, and the 81 per cent of patients achieving a final complete remission after definitive local therapy, had median overall survival figures of 95 and 97 months respectively. Overall survival and relapse-free survival in 51 patients treated with ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
1
3
0
1
Order By: Relevance
“…This study and another randomized study (397) both suggest that neoadjuvant chemotherapy can reduce the need for mutilating surgery. Similar results (and improved survival) were observed in several phase I1 studies (398)(399)(400)(401). A subgroup analysis of the VA study found that patients with N2-3 who went into complete remission on induction chemotherapy had better survival (402).…”
Section: Chemotherapysupporting
confidence: 74%
“…This study and another randomized study (397) both suggest that neoadjuvant chemotherapy can reduce the need for mutilating surgery. Similar results (and improved survival) were observed in several phase I1 studies (398)(399)(400)(401). A subgroup analysis of the VA study found that patients with N2-3 who went into complete remission on induction chemotherapy had better survival (402).…”
Section: Chemotherapysupporting
confidence: 74%
“…Options to explore for this subgroup include non-platin chemotherapy (e.g. taxanes or fluorouracil) either as induction therapy prior to radiation (48) or concurrent with radiation (49). Most interesting for this subset would be biologic therapies, such as anti–epidermal growth factor receptor monoclonal antibodies or small-molecule Bcl-2 inhibitors, with radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Nonrandomized Studies. Many series [1][2][3][4][5][6][7][8][9][10] have assessed in a nonrandomized fashion the reliability of induction chemotherapybased protocols. Most often they were small series that sometimes mixed laryngeal, hypopharyngeal, and oropharyngeal tumors or tumors amenable to partial or radical surgery.…”
Section: Induction Chemotherapy-based Strategiesmentioning
confidence: 99%